A novel ultralight three-dimensional house-of-cards titania monolith for extraordinary heavy-metal adsorption. Issue 30 (21st July 2017) - Zhao, Wenli; Chen, I.-Wei; Xu, Fangfang; Huang, Fuqiang
Abstract : Ultralight graphene foams have recently attracted attention due to their unique properties and applications, but few analogues of metal oxides are possible to prepare. Abstract : Ultralight graphene foams have recently attracted attention due to their unique properties and applications, but few analogues of metal oxides possible to prepare. Here, a new monolith of three-dimensional titania has been prepared for the first time by a simple lyophilization treatment of exfoliated titanate nanosheets in colloidal suspension. The robust and shape-formable foam is of a density as low as 5 mg cm −3 . It possesses a porous layered architecture, large interlayer spacing, and large and negatively charged specific surface area, which exhibits excellent hygroscopicity and capacity for metal cation adsorption. In both mechanical compression and heavy metal ion absorption from water, it demonstrates remarkable recyclability and fast kinetics, capable of full recovery and repeated operation. Significantly outperforming all other inorganic sorbents, it may find applications in decontamination/enrichment/recovery of toxic, radioactive and valuable metal ions.